Pengembangan LKPD Flipbook Berbasis Penguatan Karakter Kemandiri Materi Pecahan untuk Siswa Sekolah dasar - Kriswanti Kriswanti; Widiarini Widiarini; Fathul Niam (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2022)
Learning during the pandemic has several obstacles, including 1) only applying learning videos from YouTube and assignments. 2) doing assignments often assisted by parents, 3) LKPD is not yet available but using special teacher books which are less practical. This obstacle is triggered by the lack of teacher readiness in the online learning process. To solve this problem it is necessarythe Development of LKPD Flipbook Based on Character Building Independence in Fractions in Elementary Schools. The purpose of this research is to develop a practical Flipbook-Based LKPD Flipbook. Researchers developed LKPD Flipbook Based on Character Reinforcement of Fractions in Elementary Schools by using researchdevelopment of Research and Development (R&D).The ADDIE model has five stages, namely, 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The results of this study include material expert validation obtained a percentage of 78% with valid criteria, media expert validation obtained a percentage of 94% with valid criteria, linguistic expert validation obtained a percentage of 98% with valid criteria, Practicality of media by students obtained an overall percentage of 96.8% with criteria very good, independence by students obtained an overall percentage of 97.8% with very good criteria. So it can be concluded that the development of LKPD Flipbook Based on Character Building Independence of Fractional Materials meets the valid criteria and can be used.Learning during the pandemic has several obstacles, including 1) only applying learning videos from YouTube and assignments. 2) doing assignments often assisted by parents, 3) LKPD is not yet available but using special teacher books which are less practical. This obstacle is triggered by the lack of teacher readiness in the online learning process. To solve this problem it is necessarythe Development of LKPD Flipbook Based on Character Building Independence in Fractions in Elementary Schools. The purpose of this research is to develop a practical Flipbook-Based LKPD Flipbook. Researchers developed LKPD Flipbook Based on Character Reinforcement of Fractions in Elementary Schools by using researchdevelopment of Research and Development (R&D).The ADDIE model has five stages, namely, 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The results of this study include material expert validation obtained a percentage of 78% with valid criteria, media expert validation obtained a percentage of 94% with valid criteria, linguistic expert validation obtained a percentage of 98% with valid criteria, Practicality of media by students obtained an overall percentage of 96.8% with criteria very good, independence by students obtained an overall percentage of 97.8% with very good criteria. So it can be concluded that the development of LKPD Flipbook Based on Character Building Independence of Fractional Materials meets the valid criteria and can be used.